Persistence and adherence to non-vitamin K antagonist oral anticoagulant treatment in patients with atrial fibrillation across five Western European countries. Issue 11 (7th June 2021) - Komen, Joris J; Pottegård, Anton; Mantel-Teeuwisse, Aukje K; Forslund, Tomas; Hjemdahl, Paul; Wettermark, Björn; Hellfritzsch, Maja; Hallas, Jesper; Olesen, Morten; Bennie, Marion; Mueller, Tanja; Voss, Annemarie; et al.
Abstract: Aims: To assess persistence and adherence to non-vitamin K antagonist oral anticoagulant (NOAC) treatment in patients with atrial fibrillation (AF) in five Western European healthcare settings. Methods and results: We conducted a multi-country observational cohort study, including 559 445 AF patients initiating NOAC therapy from Stockholm (Sweden), Denmark, Scotland, Norway, and Germany between 2011 and 2018. Patients were followed from their first prescription until they switched to a vitamin K antagonist, emigrated, died, or the end of follow-up. We measured persistence and adherence over time and defined adequate adherence as medication possession rate ≥90% among persistent patients only. Results: Overall, persistence declined to 82% after 1 year and to 63% after 5 years. When including restarters of NOAC treatment, 85% of the patients were treated with NOACs after 5 years. The proportion of patients with adequate adherence remained above 80% throughout follow-up. Persistence and adherence were similar between countries and was higher in patients starting treatment in later years. Both first year persistence and adherence were lower with dabigatran (persistence: 77%, adherence: 65%) compared with apixaban (86% and 75%) and rivaroxaban (83% and 75%) and were statistically lower after adjusting for patient characteristics. Adherence and persistence with dabigatran remained lower throughout follow-up. Conclusion: Persistence and adherence were high among NOAC users in five Western European healthcare settings and increased in later years. Dabigatran use was associated with slightly lower persistence and adherence compared with apixaban and rivaroxaban.